2008
DOI: 10.5194/asr-2-31-2008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of turbulence in fog episodes

Abstract: Abstract. Many processes interact in a complex and highly non-linear way during the life cycle of fog, the turbulent transport being among them. Observations and analysis of turbulence are, then, fundamental to our understanding of the physical mechanisms involved with fog formation, evolution and dissipation. Data gathered by fast-response sonic anemometers are processed using wavelet methods in order to estimate turbulence parameters such as kinetic energy or fluxes during the successive stages of fog evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…On the one hand, the most common (and probably studied) fog type is radiation fog, formed as a result of the surface radiative cooling during the night (Bergot et al, 2007;Gultepe et al, 2007). Many observational and/or modelling studies have focused on this type of fog (e.g., Terradellas et al, 2008;Van der Velde et al, 2010;Bergot, 2013;Price et al, 2018, among many others), but models still have problems simulating it, especially when its formation is not imposed by the local topography (Müller et al, 2010). The characteristics of radiation fogs are variable, from short-lived, not-mixed and shallow fog events of a few meters to persistent, well-mixed and deep events of several hundreds of meters (Duynkerke, 1999;Román-Cascón et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the most common (and probably studied) fog type is radiation fog, formed as a result of the surface radiative cooling during the night (Bergot et al, 2007;Gultepe et al, 2007). Many observational and/or modelling studies have focused on this type of fog (e.g., Terradellas et al, 2008;Van der Velde et al, 2010;Bergot, 2013;Price et al, 2018, among many others), but models still have problems simulating it, especially when its formation is not imposed by the local topography (Müller et al, 2010). The characteristics of radiation fogs are variable, from short-lived, not-mixed and shallow fog events of a few meters to persistent, well-mixed and deep events of several hundreds of meters (Duynkerke, 1999;Román-Cascón et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies revealed that the balance between radiative cooling and turbulent mixing was the primary factor in radiation fog development (ROACH et al, 1976;NAKANISHI 2000;TERRADELLAS et al, 2008). Some studies focused on the radiation fogs formed in valleys, and showed that the mountain wind, urban heat island, and water surface were important in the life cycle of valley fogs (PILIE et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, radiation fog is formed through radiative cooling near the surface during the night. Over the past few decades, many observational and numerical studies have shown that turbulence was an essential factor that affected the evolution of radiation fog (e.g., Roach, 1976;Duynkerke, 1991a;Terradellas et al, 2008;Zhou and Ferrier, 2008;Ye et al, 2015; Degefie et al, 2015; Maronga and Bosveld, 2017 [3][4][5][6][7][8][9]). However, discrepancies exist among the arguments for the effects of turbulent mixing on fog formation.…”
Section: Introductionmentioning
confidence: 99%